Etiology, Clinical Features, and Diagnosis of Vulvar Lichen Sclerosus: A Scoping Review. (21st April 2020) - Singh, Nilanchali; Ghatage, Prafull
Abstract : Objective . Vulvar lichen sclerosus (VLS) is a chronic inflammatory disorder, which affects women of all ages. With numerous controversies as regards to the nomenclature, diagnosis and its association with neoplastic conditions, we decided to conduct a scoping review on this subject. Data Source . A review protocol was developed, and the Knowledge Resource Services website was used to do a search of articles pertaining to VLS with keywords "Vulvar, " "Vulval, " "diagnosis, " "lichen sclerosus et atrophicus, " "kraurosis, " "vulvar dystrophy, " and "Lichen Sclerosus". Study Selection . The search was limited to published data from the last ten years, i.e., from July 2009 onwards and in the English language. A total of 338 articles pertaining to VLS were obtained. Older data were accessed if particular information was sought for. Results & Conclusion . The presentation is bimodal, i.e., one in prepubertal girls (average age: 7.6 years) and the other in peri- and postmenopausal women (average age: 52.6 years). However, many cases also present during reproductive years. Studies suggest a multifactorial origin as far as etiology is concerned, including a genetic, autoimmune, hormonal, and local infectious background. It affects the genital labial, perineal, and perianal areas and manifests as a patchy, thin, glistening, ivory-white area. Diagnosis is mainly based on clinical features. Biopsy is seldom required. It has been well established as a precursor lesion of dVIN and vulvar carcinoma.